Optimized preparation and characterization of CLEA-lipase from cocoa pod husk - Yusof, Faridah; Khanahmadi, Soofia; Amid, Azura; Mahmod, Safa Senan; Mahat, Mohd Khairizal (Elsevier, 2014)
Cross-linked enzyme aggregate (CLEA) is easily prepared from crude enzyme and has many advantagesto the environment and it is considered as an economic method in the context of industrial biocatalysiscompared to free enzyme. In this work, a highly active and stable CLEA-lipase from cocoa pod husk (CPH)which is a by-product after removal of cocoa beans, were assayed for their hydrolytic activity and char-acterized under the optimum condition successfully. Face centered central composite design (FCCCD)under response surface methodology (RSM) was used to get the optimal conditions of the three signif-icant factors (concentration of ammonium sulfate, concentration of glutaraldehyde and concentrationof additive) to achieve higher enzyme activity of CLEA. From 20 runs, the highest activity recorded wasaround 9.407 U (83% recovered activity) under the condition of using 20% saturated ammonium sulfate,60 mM glutaraldehyde as cross-linker and 0.17 mM bovine serum albumin as feeder. Moreover, the opti-mal reaction temperature and pH value in enzymatic reaction for both crude enzyme and immobilizedwere found to be 45◦C at pH 8 and 60◦C at pH 8.2, respectively. A systematic study of the stability of CLEAand crude enzyme was taken with regards to temperature (25–60◦C) and pH (5–10) value and in bothfactors, CLEA-lipase showed more stability than free lipase. The Kmvalue of CLEA was higher comparedto free enzyme (0.55 mM vs. 0.08 mM). The CLEA retained more than 60% of the initial activity after sixcycles of reuse compared to free enzyme. The high stability and recyclability of CLEA-lipase from CPHmake it efficient for different industrial applications.